Spin-dependent energy gap oscillations in the ultra-short carbon nanotube (5, 5). (October 2015) - Tuchin, A V; Popov, S V; Glushkov, G I; Bityutskaya, L A
Abstract: Results of the numerical simulation of an electronic structure of an ultrashort singlewalled carbon nanotube (5, 5) at singlet and triplet states were presented. An antiphase energy gap oscillation on the length of the ultrashort nanotube (5, 5) at singlet and triplet states was revealed. It was found that the ground state of the nanotube is singlet, herewith the energy of the singlet-triplet transition corresponds to the energy value of visible andIR-radiation.